Some New Classes of Extended General Mixed Quasi-Variational Inequalities - Muhammad Aslam Noor; Khalida Inayat Noor (Abstract and Applied Analysis)
We consider and study a new class of variational inequality, which is called the extended general mixed quas-variational inequality. We use the auxiliary principle technique to study the existence of a solution of the extended general mixed quasi-variational inequality. Several special cases are also discussed. Results proved in this paper may stimulate further research in this area.